2020
DOI: 10.3174/ajnr.a6883
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Acute Stroke Imaging

Abstract: Artificial intelligence technology is a rapidly expanding field with many applications in acute stroke imaging, including ischemic and hemorrhage subtypes. Early identification of acute stroke is critical for initiating prompt intervention to reduce morbidity and mortality. Artificial intelligence can help with various aspects of the stroke treatment paradigm, including infarct or hemorrhage detection, segmentation, classification, large vessel occlusion detection, Alberta Stroke Program Early CT Score grading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 66 publications
0
76
0
3
Order By: Relevance
“…An overview of several segmentation methods with a comparison to the present study is shown in Table 5 of the Supplementary Appendix. AI-based image analysis is increasingly applied in clinical practice, especially in the field of acute stroke [13]. Despite this evolution, there are still a limited number of AI-based applications commercially available to assess ICHs in patients with acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…An overview of several segmentation methods with a comparison to the present study is shown in Table 5 of the Supplementary Appendix. AI-based image analysis is increasingly applied in clinical practice, especially in the field of acute stroke [13]. Despite this evolution, there are still a limited number of AI-based applications commercially available to assess ICHs in patients with acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The hierarchy of AI methods is as follows: 1. deep learning (DL) is a subset of 2. representation learning (RL), which is a subset of 3. machine learning (ML), which represents a subset of 4. AI [16]. Classic medical algorithms consist of three steps: 1. preprocessing of medical images, 2.…”
Section: Stroke Managementmentioning
confidence: 99%
“…Large vessel occlusion (LVO) detection is essential for identifying potential candidates who could benefit from mechanical thrombectomy. CTA is typically the preferred technique for large vessel occlusion detection, but noncontrast-enhanced CT (NCCT) scans can also be used to localize the site of occlusion (Figure 2), and decrease the necessary amount of contrast media and reserve it only for angiography during recanalization procedure [16].…”
Section: Artery Occlusion Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of stroke care, artificial intelligence and wearable sensors have primarily been used to identify risk factors such as detection of atrial fibrillation using smartwatches [ 5 , 6 ]—reviewed in [ 7 ]—and blood pressure estimation based on photoplethysmography to assess hypertension [ 8 ]. Within stroke imaging, artificial intelligence has been used to perform several imaging processing tasks, reviewed in [ 9 , 10 ]. However, most of these applications are based on data gathered with a human interpreter in mind, such as the visual aspects of a skin lesion or the digital reconstruction of a chest X-ray.…”
Section: Introductionmentioning
confidence: 99%